2013
DOI: 10.1097/bcr.0b013e3182642c27
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Early Methadone Initiation in Critically Injured Burn Patients

Abstract: Numerous studies have identified strategies to reduce mechanical ventilation duration by targeting appropriate sedation levels. However, applicability of these strategies to critically injured patients with burn injury has not been established. At our medical center, methadone is commonly used early in the care of burn patients to treat background pain and limit the development of opioid tolerance. The aim of this study is to evaluate the effect of early methadone initiation in critically injured burn patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…In adult intensive care, methadone has been used successfully to facilitate narcotic weaning, reducing the duration of opioid infusion and the length of exposure to mechanical ventilation in specific populations . Transitioning to a long‐acting opioid such as methadone is a generally accepted approach to narcotic weaning in pediatric patients .…”
Section: Introductionmentioning
confidence: 99%
“…In adult intensive care, methadone has been used successfully to facilitate narcotic weaning, reducing the duration of opioid infusion and the length of exposure to mechanical ventilation in specific populations . Transitioning to a long‐acting opioid such as methadone is a generally accepted approach to narcotic weaning in pediatric patients .…”
Section: Introductionmentioning
confidence: 99%
“…1,5,[29][30][31] Methadone is a potent analgesic, is an effective alternative analgesic in opioid-tolerant patients, is used to treat opioid dependence, and can also attenuate central sensitization. 5,29,30,32 Jones et al 5 suggested that early use of methadone leads to better outcomes for burn patients. In fact, in a retrospective pilot study, Jones found that mechanically ventilated patients who received early methadone treatment had an increase in the number of ventilator-free days.…”
Section: Nonopioid Adjunctsmentioning
confidence: 99%
“…7,8 Poor pain control also decreases patient compliance with rehabilitation therapy and negatively affects the confidence of the patient in the burn team. 1,5 Thompson et al 9 showed that patient's discomfort during medical procedures impedes on wound care, increases the risk of wound infection, decreases the patient's ability to perform the usual range of motion exercises, increases psychological stress, and is associated with longer hospitalizations.…”
mentioning
confidence: 98%
See 1 more Smart Citation